The mediating role of medical coping modes between stigma and quality of life in patients undergoing lung cancer surgery: a cross-sectional study - Fengyan Ma; Wei Zheng; Weining Wang; Na Zhang; Yan Liu (BMC Cancer)
Abstract Background Stigma has been identified as a significant factor impacting the health of lung cancer patients. However, the relationship between stigma, medical coping modes, and quality of life (QoL) has not been thoroughly examined. Objective This study aimed to explore the associations between stigma, medical coping modes, and QoL in patients undergoing lung cancer surgery. Methods A total of 304 surgical patients participated in an online survey, which included sociodemographic data, the Lung Cancer Stigma Scale, the Medical Coping Modes Scale, and the Quality of Life Scale. Data analysis was performed using SPSS 24.0, and structural equation models were constructed using AMOS 24.0. The Bootstrap method was employed to test the mediating hypotheses. Results The mean QoL score was 150.53 ± 15.54, showing significant associations with medical coping modes and stigma. Stigma was negatively correlated with QoL (r = -0.668, p < 0.01). Confrontation was positively associated with QoL (r = 0.339, p < 0.01), while resignation and avoidance were negatively correlated with QoL (r = -0.584, r = -0.500, p < 0.01). Stigma’s effect on QoL was partially mediated by confrontation, resignation, and avoidance, with effect sizes of -0.051, -0.190, and − 0.098, respectively, accounting for 35.1% of the total effect. Conclusion Preoperative NSCLC patients in China experience moderate stigma, which detrimentally affects their QoL. Confrontation, resignation, and avoidance play mediating roles in this relationship. These findings offer new perspectives for developing interventions to improve QoL by addressing stigma and coping strategies.